Effect of Wood Flour Content and Cooling Rate on Properties of Rubberwood Flour/Recycled Polypropylene Composites - Thanate Ratanawilai (Advanced Materials Research, 2012)
The present article summarizes an experimental study on the mechanical and thermal behavior of recycled polypropylene composites reinforced with rubberwood flour. Different compositions were varied to investigate mechanical strengths, melting temperature, storage modulus, and loss modulus. It was observed that the tensile and flexural strengths decreased with the increase of wood flour content. Furthermore, the air cooled composites showed improved properties in comparison with the water cooled composites. The melting and crystallization temperature results presented a weak influence of increased wood flour content on composites. However, dynamic mechanical thermal analysis showed an increase in the storage and loss modulus.